The Effect of Reading Fluency in Developing Reading Comprehension - Hagani, Hayet (My University, 2017)
The present research aims at examining the strength of the correlation between reading fluency and reading comprehension. It takes the case of first year secondary school (literary stream) at“Ben Guella Touati” at Mostaganem, and it has been carried out involving 47 participants who study English as foreign language During the academic year 2016-2017. The hypothesis for this study is that enhancing students’ comprehension is affected by providing sufficient instructions to develop their fluency. In order to verify the hypothesis, a questionnaire and practical test are administrated to students to gather data about the influence of reading fluency on reading comprehension. In addition to a questionnaire administrated to teachers in order to investigate the nature of this relationship. The data collected from the materials used indicates that fluency and comprehension are intertwined and achieving fluency contributes to achieving comprehension. On the basis of the conclusions drawn from this experiment, some pedagogical implications are proposed to help students progress their fluency, and some instructions and principles are provided that should be taken into consideration by teachers so as to achieve the reading process.
The Case of First Year Secondary School of Ben Gella Touati -Mostaganem-
Keywords: Reading fluency; Reading comprehension; Instructions; Reading process